2013
DOI: 10.1242/jcs.120196
|View full text |Cite
|
Sign up to set email alerts
|

Regulated recycling of mutant CFTR partially restored by pharmacological treatment

Abstract: SummaryEfficient trafficking of the cystic fibrosis transmembrane conductance regulator (CFTR) to and from the cell surface is essential for maintaining channel density at the plasma membrane (PM) and ensuring proper physiological activity. The most common mutation, F508del, exhibits reduced surface expression and impaired function despite treatment with currently available pharmacological small molecules, called correctors. To gain more detailed insight into whether CFTR enters compartments that allow correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…Note that VX-809 increased the steady-state protein levels of both the wt and mutant ABCA4. However, even though C18 and VX-809 are similar classes of compounds (16), the effect of C18 on the mutants was greater than that of VX-809.…”
Section: Discussionmentioning
confidence: 84%
“…Note that VX-809 increased the steady-state protein levels of both the wt and mutant ABCA4. However, even though C18 and VX-809 are similar classes of compounds (16), the effect of C18 on the mutants was greater than that of VX-809.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, ENaC and CFTR that are both regulated by Nedd4-2 also seem to be regulated by such a PKA-mediated dual response. PKA activation leads to increased surface expression of both ENaC and CFTR (12,31). In addition, the open probability of ENaC and the activity of CFTR are increased in response to activation of PKA (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent data have also reported that the Rab11 machinery is involved in the recycling of corrector-rescued F508del-CFTR, confirming that chemical correction redirects F508del trafficking from the degradation pathway to regulated recycling -with the proteins that are involved in the process being obvious targets for the improvement of the available correctors. 22 Interestingly, this study reports an improvement in mutant CFTR stability due to decreased lysosomal accumulation/targeting when correctors are added acutely, suggesting that i) the compounds may also act on peripheral quality control and ii) that temperature/corrector-promoted F508del-CFTR escape from the ER does not correspond to its full correction in terms of misfolding. 22 Rab4 was found initially to have only a minor role in CFTR direct recycling to the PM from early endosomes in BHK cells.…”
Section: Regulation Of Cftr Membrane Trafficking By Rab Gtpasesmentioning
confidence: 83%
“…22 Interestingly, this study reports an improvement in mutant CFTR stability due to decreased lysosomal accumulation/targeting when correctors are added acutely, suggesting that i) the compounds may also act on peripheral quality control and ii) that temperature/corrector-promoted F508del-CFTR escape from the ER does not correspond to its full correction in terms of misfolding. 22 Rab4 was found initially to have only a minor role in CFTR direct recycling to the PM from early endosomes in BHK cells. 13 Later studies reported that overexpression of Rab4 inhibits CFTR-mediated current in the colonic epithelial cell line HT29 and that, reversely, Rab4 inhibition (by overexpression of an anti-Rab4 antibody) reverses the observed inhibition of CFTR.…”
Section: Regulation Of Cftr Membrane Trafficking By Rab Gtpasesmentioning
confidence: 83%
See 1 more Smart Citation